Novel gelling pectins from Zea mays husks' agro-industrial residue and their interaction with calcium and iron (II). (November 2021) - Higuera-Coelho, Ricardo A.; Lizarraga, Leonardo; Ponce, Nora M.A.; Stortz, Carlos A.; Rojas, Ana M.; Bernhardt, Dana C.; Fissore, Eliana N.
Abstract: Pectin enriched fractions were isolated from maize husks. High-power ultrasound (US) pretreatment increased the yield in pectin extraction performed through alkaline hydrolysis of ferulate-bridges followed by hydrolysis with cellulase. The fraction obtained (MP-US) was a homogalacturonan (67% w/w uronic acids, UA). MP-US showed an average molecular weight ( Mw ) of 108, 600 Da with a polydispersity ( Mw / Mn ) of 3.45, which means that the chain lengths are different as is generally observed in pectins even of the same origin. Atomic force microscopy confirmed non-aggregated thin fibres (77-71 nm contour-length), which may justify the exceptional water solubility. Without US, the fraction obtained (MP) was also a homogalacturonan (63% w/w UA) of 166, 000 Da of Mw with higher polydispersity (4.24). MP showed aggregated fibres, coinciding with its difficult dissolution in water, as usually observed with pectins. Hydrodynamic diameter at pH 6.0 was lower for MP-US (122 nm) than for MP (350 nm). MP-US and MP interacted with essential human nutrients like calcium and iron (II) in a different manner. Both pectins were overly sensitive to calcium (1.25 × 10 −4  mol/g UA), which electrostatically cross-linked the pectins in thermo-irreversible gels at pH 6.0. Instead, iron (II) formed thermo-reversible "weak-type" gel networks due to the predominance of hydrogen bonding. These features could be relevant for the intestinal bio-accessibility of calcium and iron (II). In conclusion, the novel pectins extracted from corn husks can be useful as texture modifiers in food and pharmaceutical applications, with potential bioactivity for the delivery of essential nutrients, while allowing valorisation of corn residues.